ANALISIS KEDISIPLINAN ANGGOTA POLRI DI POLSEK BANDONGAN POLRES MAGELANG KOTA - Muchammad Irchamudin; Muda Setia Hamid (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
Discipline is the operative function of the most important human resource management because the better the discipline of employees, the higher the work performance that can be achieved. Without good discipline, it is difficult for organizations / companies to achieve optimal results. Discipline cannot be separated from the police because one of the police functions is to hold the function of state government in the field of law enforcement, protection, service and service to the community, as well as community guidance in order to guarantee the orderly and till the law and the deepest of the peace of society to realize security and public order. Therefore a member of the National Police is required to have a high level of discipline to support its duties. This study aims to identify the factors that cause discipline of members of the National Police at the Bandongan Police Station of the Magelang City Police have not been optimal in addition to knowing efforts to improve the discipline of members of the National Police in the Bandongan police station. The data collection technique used is interviews, observation and documentation. Data analysis methods use data reduction, display data, and data verification. The results showed that the discipline of the National Police Members in the Bandongan Police was quite good, but there were some things that were not optimal, for example the discovery of several members who arrived late when implementing apples, the use of official official clothing, the attitude of members who did not match the rules and several members which is not orderly in terms of online attendance. The causes of some not disciplined members include poor time management, a low level of awareness of members and less obedient to applicable regulations. Efforts to improve the discipline of members of the National Police at the Bandongan police station, among them by increasing supervision of unsuppled members and decisive actions against the members.